Enhanced snapshot with intelligent optimal replacement model for hostel maintenance management based on failure data - Ab Wahab, Yuseni (UTeM, 2016)
Malaysia is presently in the intermediary phase of growth and industrialization where many building tasks are being prepared. The project of public building includes educational buildings, hospital buildings and government buildings (Hilde and Theo Van, 2011; Wilkinson and Reed, 2010). A number of building defects have arisen and been reported officially by the mass media, with several relating to educational buildings (Mydin et al., 2014). There are numerous defects which are common to hostel building components, such as roofs, walls, floors, ceilings, toilets, doors and windows. These defects may cause unexpected accidents and even death (Soleimanzadeh and Mydin, 2013). For example, on 12 September 2005, a teacher fell to his death when a decayed plywood floor of a two- storey school block in SJK (C) Keat Hwa, Kedah gave away. It is believed that the floor was ruined by termites (Isa et al., 2011). Based on the cases reported, defects can be concluded as fatally disparaging and critical because they bring impairment to their users and the building itself, causing damage, serious injury and death (Susan Aryee, 2011). Therefore, a study is important to investigate the contributing factors of those defects in order to create a safe buildings (Khozaei, 2011; Wahab and Hamid, 2011).Then a remediation plan can be developed based on the respective defects and failure to mitigate the impacts and also improve current conditions (Mydin et al., 2011). Users, investors, and public officials became more concerned after hearing about critical incidents involving the sudden collapse and failure of infrastructure components. Public awareness of these incidents and identification of potential failure areas have led to a perception of an infrastructure crisis (Naser et al., 2011). Table 1.1 provides failure issues, none of which are due to natural disasters, such as earthquakes or tornadoes, but are rather as a result of other causes, most probably lack of maintenance and repair, inadequate inspection and condition evaluation, insufficient funding, or more generally, inadequate management.